Analysis of Student Research Culture and Its Strengthening at Raden Fatah State Islamic University Palembang and Raden Intan State Islamic University Lampung - Kusnadi Kusnadi; Ahmad Soleh Sakni; Bukhori Abdul Shomad (JIA (Jurnal Ilmu Agama), 2023)
This study aims to look at how the Al-Quranic Science and Tafsir (IAT) Department at Raden Fatah State Islamic University and Raden Intan State Islamic University are making it easier for students to do research. This type of research is library research with a qualitative approach. The method used in this study is descriptive, namely revealing data through a person's dialogue, either orally or in writing, and behavior that can be observed. Taking all of this into account, the study's results show that the way IAT students at the two universities do research is still the most common way to do research in libraries. This can be seen in some of their research, both in the study of themes, the thoughts of Mufassir, the study of the book of interpretation, and the method of the book of interpretation. While the methods used in their research are tafsir-related, they are analysis, comparison, and thematic. In the meantime, field studies or the living Qur'an have not been the most common way to do research. The classification of student research includes three things: thematic themes, comparisons, and character studies. Second, to strengthen the capacity of students in research, several activities are carried out, including training activities for writing scientific papers by strengthening research methods, followed by the practice of writing scientific papers through the writing class program. The goal is to help students improve their writing skills and successfully publish articles in national journals, as well as to publish anthologies and Bunga Rampai Books on Religion & Society, Revealing Various Phenomena of Tradition, and Religious Problems. IAT students also take part in an academic writing class called ATLAS (Academic Writing Class). The writing class training results in students being able to become resource persons at international seminars held in the PTKIN environment.